Enhancing Inclusive Talent Management and Financial Management Literacy through Digitalization to Improve Human Resource Performance - Zandra Dwanita Widodo; Susilaningtyas Budiana Kurniawati; Retnoning Ambarwati; Eny Kusumawati (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to examine how strengthening inclusive talent management and financial management literacy through digitalization can improve human resource performance at TK Aisyiyah X Jaten Karanganyar. Research Methodology: A descriptive qualitative approach with a case study design was employed. Data were collected through Focus Group Discussions and in-depth interviews with the principal, teachers, and administrative staff. The data were analyzed using NVivo 14 through data reduction, coding, data display, verification, and thematic analysis. Results: The findings identified four major themes: management, development, finance, and performance. Management emphasized the importance of communication, teachers’ roles, and organizational structure. Development highlighted the need for continuous digital training despite challenges such as limited facilities and resistance to change. Finance showed that financial literacy and administrative digitalization were essential for transparency and accountability. Performance stressed the value of digital-based evaluation in monitoring teacher competence, training outcomes, and the effectiveness of digital transformation. Conclusions: Digitalization functions as the key link connecting talent management, financial literacy, and performance evaluation. It is therefore necessary for TK Aisyiyah X Jaten Karanganyar to pursue sustainable educational transformation, strengthen financial literacy, and consistently apply technology-based performance evaluation. Limitations: The study focused on a single institution, which limits the broader generalizability of the findings. Contributions: This study contributes to educational management by providing insights into inclusive talent management, financial literacy, and digital transformation in early childhood education. The findings may inform school leaders, teachers, administrative staff, and policymakers in developing more effective and sustainable institutional strategies.